2020
DOI: 10.1177/0735633120952067
|View full text |Cite
|
Sign up to set email alerts
|

Conversation Technology With Micro-Learning: The Impact of Chatbot-Based Learning on Students’ Learning Motivation and Performance

Abstract: This study investigated the impact of a chatbot-based micro-learning system on students’ learning motivation and performance. A quasi-experiment was conducted with 99 first-year students taking part in a basic computer course on number system conversion. The students were assigned to a traditional learning group or a chatbot-based micro-learning group. After the experiment, both groups achieved a comparable performance, suggesting that students are sufficiently competent to learn independently in the chatbot-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(133 citation statements)
references
References 38 publications
6
66
0
1
Order By: Relevance
“…To summarize, this study showed that intrinsic the motivating factor challenging goals predicts decreased anxiety in a group of participants of e-learning-based computer programming courses. These findings are, to some extent, in line with those of previous research, suggesting that intrinsic learning motivation is related to better learning outcomes and higher satisfaction with the learning process, whereas extrinsic learning motivation is related to higher stress levels [35,36,67]. However, it is partially clear why only one intrinsic motivational factor (challenging goals) contributed to the decreased anxiety [107], and why this pattern was not apparent in the group of other e-learners, which would be in line with many other studies [33,[107][108][109][110][111].…”
Section: Learning Motivating Factors Partially Predict Anxiety Levelsupporting
confidence: 91%
See 1 more Smart Citation
“…To summarize, this study showed that intrinsic the motivating factor challenging goals predicts decreased anxiety in a group of participants of e-learning-based computer programming courses. These findings are, to some extent, in line with those of previous research, suggesting that intrinsic learning motivation is related to better learning outcomes and higher satisfaction with the learning process, whereas extrinsic learning motivation is related to higher stress levels [35,36,67]. However, it is partially clear why only one intrinsic motivational factor (challenging goals) contributed to the decreased anxiety [107], and why this pattern was not apparent in the group of other e-learners, which would be in line with many other studies [33,[107][108][109][110][111].…”
Section: Learning Motivating Factors Partially Predict Anxiety Levelsupporting
confidence: 91%
“…Moreover, emotions are essential factors in determining whether the student will master the exercise of learning to program in the short and long terms [34]. Some studies suggest that intrinsic learning motivation is related to better learning outcomes and higher satisfaction with the learning process, whereas extrinsic motivation is related to higher stress levels [35,36].…”
Section: Learning and Emotional Healthmentioning
confidence: 99%
“…In another study conducted to teach programming, a positive significant difference was observed in the germane load and sub-cognitive layer outputs of students using chatbots (Abbasi et al, 2019 ). On the other hand, Yin et al ( 2020 ) conducted a study with university students that found the positive effects of chatbot applications on the intrinsic motivation of students in the experimental group, but they did not find much difference between students’ performances. The use of voice assistants even though they did not cause a significant difference in the learning outcomes, whose effectiveness in learning has been tested by Sáiz-Manzanares et al ( 2020 ), was found to be a great aid in learning processes as it promotes the development of self-regulated learning, is functionally evaluated by university students in accessing information during the pandemic, and that students’ satisfaction with their learning increased.…”
Section: Conclusion and Discussionmentioning
confidence: 98%
“…As a result of this research, it was determined that the chatbot had a significant effect on student achievement and that students showed greater interest. In a study conducted by Yin et al ( 2020 ) with undergraduate students, the subject of Digital Systems was presented to the experimental group with the help of a chatbot application. As a result of the research, while they did not find a significant difference between the performance levels of the experimental and control groups, it was observed that the intrinsic motivation of the students in the experimental group was higher,…”
Section: Introductionmentioning
confidence: 99%
“…In the face of this new normal, it is therefore necessary to pay greater attention to the potential of mobile devices as flexible learning alternatives. Because the mobile learning market is rapidly growing, students can now benefit from various mobile learning resources, such as micro content (Yin et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%